Acoustic Radiation Force Impulse Elastography for the Non-Invasive Evaluation of Hepatic Fibrosis in Non-Alcoholic Fatty Liver Disease Patients: A Systematic Review & Meta-Analysis. - Haixia Liu; Jing Fu; Ruixia Hong; Li Liu; Fang Li (PLoS ONE)
Background In order to better monitor non-alcoholic fatty liver disease (NAFLD) patients at higher risk for HCC, there is a need for non-invasive diagnostic approaches to screen for the presence of advanced fibrosis in these patients. The aim of this systematic review and meta-analysis will be to evaluate the diagnostic efficacy of ARFI elastography in detecting hepatic fibrosis in NAFLD patients. Methods Relevant studies were identified from systematic searches of several major electronic databases (PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials). The primary outcomes were the summary sensitivity, summary specificity, the diagnostic odds ratio, and the summary receiver operating characteristic curve (SROC) of ARFI elastography in detecting significant fibrosis (defined as 4>F≥2) in NAFLD patients. Study quality was assessed using the Quality Assessment of Studies of Diagnostic Accuracy included in Systematic Review (QUADAS-2). Results The summary sensitivity and specificity of ARFI in detecting significant fibrosis were 80.2% (95% confidence interval (CI): 0.758-0.842; p = 0.0000) and 85.2% (95% CI: 0.808-0.890), p = 0.1617), respectively. The pooled diagnostic odds ratio of ARFI in detecting significant fibrosis was 30.13 (95% CI: 12.08-75; chi-squared = 14.59, p = 0.0237). The area under the SROC curve (AUC) was 0.898 (standard error (SE): 0.031) with a Q* index of 0.830 (SE: 0.033). Conclusions ARFI elastography appears to be modestly accurate in detecting significant fibrosis in NAFLD patients. Future studies in this field should provide head-to-head comparisons of ARFI elastography versus other elastographic imaging modalities in NAFLD patients.